The Price of Plenty: India’s rice surplus and global market effects - Mirzabaev, Alisher; Zwinger, Jeremy (International Rice Research Institute, 2025)
• India’s public rice reserves are currently nearly three times the official buffer norms, creating high warehousing and fiscal strains. • This oversupply situation in India will have massive global effects on the rice industry. • Following the end of India's export ban in 2024, prices in the rice market have already fallen by about $200 per metric ton, with challenges now emerging to find buyers even at these reduced prices.